Choosing a Provider: What Factors Matter Most to Consumers and Patients?. (January 2022) - Kozikowski, Andrzej; Morton-Rias, Dawn; Mauldin, Sheila; Jeffery, Colette; Kavanaugh, Kasey; Barnhill, Grady
Enhancing consumer and patient choice has been proposed as a means to improve care quality and reduce health-related costs. Choosing a medical provider is one of the most critical and often complex decisions patients make about their health care. We investigated the perceived importance of factors patients may consider when selecting a practitioner and if rated importance of the factors varies with their characteristics and prior experiences with different types of clinicians (physicians, physician assistants, and nurse practitioners). Participants most often identified medical license, certification, and whether the provider accepts the patients' health insurance as important, while provider type, others' recommendations, and online reviews were among the least important. We found wide-ranging differences based on patient characteristics. Prior experience with providers was also a strong determinant of patterns of factors patients considered valuable. Policy-makers, health systems, insurers, and providers need to take into account that patients rely on a range of factors that vary based on their distinct needs, backgrounds, and previous experiences—requiring tailored information to make more informed decisions.